Heat Shock Proteins: Agents of Cancer Development and Therapeutic Targets in Anti-Cancer Therapy - Yun, Chul Won (Cells, 2019)
Heat shock proteins (HSPs) constitute a large family of molecular chaperones classified by their molecular weights, and they include HSP27, HSP40, HSP60, HSP70, and HSP90. HSPs function in diverse physiological and protective processes to assist in maintaining cellular homeostasis. In particular, HSPs participate in protein folding and maturation processes under diverse stressors such as heat shock, hypoxia, and degradation. Notably, HSPs also play essential roles across cancers as they are implicated in a variety of cancer-related activities such as cell proliferation, metastasis, and anti-cancer drug resistance. In this review, we comprehensively discuss the functions of HSPs in association with cancer initiation, progression, and metastasis and anti-cancer therapy resistance. Moreover, the potential utilization of HSPs to enhance the effects of chemo-, radio-, and immunotherapy is explored. Taken together, HSPs have multiple clinical usages as biomarkers for cancer diagnosis and prognosis as well as the potential therapeutic targets for anti-cancer treatment.